2019
DOI: 10.1029/2019jd031701
|View full text |Cite
|
Sign up to set email alerts
|

Optical Modeling of Black Carbon With Different Coating Materials: The Effect of Coating Configurations

Abstract: In this work, an assembly of coating structures is generated for coated black carbon (BC) based on two different coating methods with limited tunable parameters. By defining typical parameters, the proposed coating structures show great agreement with the detailed morphologies of coated BC particles in the atmosphere. Our models can accurately reproduce the measured linear backscattering depolarization ratio (LDR). We noticed that BC with spherical coatings (Configuration E) has difficulty estimating large LDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 107 publications
0
26
0
Order By: Relevance
“…However, as coating materials increase, the fractal structure of BC may be damaged. Chakrabarty and Heinson [71] used a complex BC model by assuming that coating materials surround BC to calculate BC optical properties; Ishimoto et al [72] proposed an internally mixed BC model based on the artificial surface tension; Luo et al [48] have proposed BC models with different coating materials. However, these models are complex and computationally expensive.…”
Section: Generation Of Bcmentioning
confidence: 99%
“…However, as coating materials increase, the fractal structure of BC may be damaged. Chakrabarty and Heinson [71] used a complex BC model by assuming that coating materials surround BC to calculate BC optical properties; Ishimoto et al [72] proposed an internally mixed BC model based on the artificial surface tension; Luo et al [48] have proposed BC models with different coating materials. However, these models are complex and computationally expensive.…”
Section: Generation Of Bcmentioning
confidence: 99%
“…Lidar ratios and depolarization ratios measured simultaneously at both 355 and 532 nm wavelengths are a prerequisite in efforts to successfully homogenize the overall Aeolus-CALIPSO data set of smoke optical properties later on. Simultaneously measured lidar ratios and depolarization ratios are also important parameters in aerosol typing efforts (see, e.g., Burton et al, 2012Burton et al, , 2015Groß et al, 2013;Nicolae et al, 2018;Papagiannopoulos et al, 2018) with lidars from ground and in space to improve optical models developed to simulate the smoke optical properties as a function of particle shape and size characteristics and composition (e.g., Kahnert, 2017;Mishchenko, 2018, 2020;Luo et al, 2019;Gialitaki et al, 2020). Thus, our Punta Arenas lidar observations in January 2020 can be regarded as an important contribution to the global library of aerosol optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…R c = 50R g and R c = R g were assumed to represent the film and spherical coatings, and are named Model B and Model C, respectively. In our previous study (Luo et al, 2019), we have demonstrated that our proposed models can greatly simulate the internally mixed BC morphologies and reproduce the measured absorption as well. For more details about the algorithm to generate the coated BC, please refer to Luo et al (2019), and the typically generated morphologies are shown in Figure 2 and the Figures S1-S2 of Luo et al (2019).…”
Section: Morphologiesmentioning
confidence: 71%
“…Non-spherical aerosol models show more excellent performance on reproducing the measurements even though Mie theory was commonly used in remote sensing and climate modeling (Bi et al, 2018;He et al, 2016He et al, , 2015Chakrabarty et al, 2007;Luo et al, 2019). In the atmosphere, BC can be mixed with BrC, and the mixing states are commonly divided into externally mixed and internally mixed.…”
Section: Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation